The Youth of Early Modern Women - Cohen, Elizabeth; Reeves, Margaret (Amsterdam University Press, 2018)
Through fifteen varied case studies that draw on a rich array of primary sources, this collection of essays makes the novel claim that early modern European women, like men, had a youth.European culture recognized that, between childhood and full adulthood, early modern women experienced distinctive physiological, social, and psychological transformations. Drawing on two mutually shaped layers of inquiry--cultural constructions of youth and lived experiences--the essays examine a rich array of primary sources, including literary and autobiographical works, conduct literature, asylum and judicial records, drawings, and material culture. The geographical and temporal ranges traverse England, Ireland, Italy, France, Spain, Mexico, Germany, and the Netherlands from the sixteenth to the eighteenth centuries. It brings fresh attention to representations of female youth, the training for adulthood, their own life writings, courtship and the emergent sexual lives of young unmarried women.